2018
DOI: 10.1039/c7qo01073g
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of sulfur dioxide via a radical process: an efficient route to sulfonyl compounds

Abstract: This review is focused on the recent advances in the chemistry of sulfur dioxide fixation through a radical process. Diverse sulfonyl compounds can be obtained efficiently under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 306 publications
(68 citation statements)
references
References 105 publications
2
62
0
Order By: Relevance
“…Since the submission of this review several new methods for the synthesis of molecules containing sulfonyl‐functionalities and one review article have been reported in the literature, highlighting the tremendous activity in this research area …”
Section: Discussionmentioning
confidence: 99%
“…Since the submission of this review several new methods for the synthesis of molecules containing sulfonyl‐functionalities and one review article have been reported in the literature, highlighting the tremendous activity in this research area …”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, insertion of sulfur dioxide via radical processes has been developed rapidly for the synthesis of sulfonyl compounds. [13,14] Generally, DABCO·(SO 2 ) 2 [15] or inorganic sulfites [16] are used as the sulfur dioxide surrogates. Various carbon radical precursors [17][18][19] have been utilized in the transformations.…”
Section: Introductionmentioning
confidence: 99%
“…It summarizes the literature data, mainly from 2000 to 2018. Radical insertion of sulfur dioxide into organic molecules with the formation of S–N bonds has already been summarized and is not included in this review. The review is divided into chapters in accordance with the classes of compounds synthesized: firstly the synthesis of linear molecules is described, after which heterocyclization reactions and formation of structures containing more than two heteroatoms in succession are discussed.…”
Section: Introductionmentioning
confidence: 99%